Investigation on the Access Log Pattern of the Corporate Social Responsibility UUMWiFi among Changlun’s Community - Mohamad Mohsin, Mohamad Farhan; Abdul Hamid, Mohd Noor; Ahmad Mustaffa, Nurakmal; Ramli, Razamin; Abdullah, Kamarudin (International Journal of Interactive Mobile Technologies (iJIM), 2019)
CSR UUMWiFi is a CSR project under Universiti Utara Malaysia (UUM) that provides unlimited free internet connection for the Changlun community. Launched in 2015, the service has accumulated a huge number of users with diverse background and interest. This paper aims to uncover interesting service users’ behavior by mining the usage data. To achieve that, the access log for 3 months with 24,000 online users were downloaded from the Wi-Fi network server, pre-process and analyzed. The finding reveals that there were many loyal users who have been using this service on a daily basis since 2015 and the community spent 20-60 minutes per session. Besides that, the social media and leisure based application such YouTube, Facebook, Instagram, chatting applications, and miscellaneous web applications were among the top applications accessed by the Changlun community which contributes to huge data usage. It is also found that there were few users have used the CSR UUM WiFi for academic or business purposes. The identified patterns benefits the management team in providing a better quality service for community in future and setting up new policies for the service.